(untitled) (Modern education and development, 2025)
Currently, more than 250 red blood cell antigens have been identified, which are grouped into more than 20 antigen systems. 13 systems are of clinical significance: ABO, Rh-Hr, Kell, Duffy, MNSs, Kidd, Lewis, Lutheran, Diego, Auberger, Dombrock, and I.